SUSTAINABILITY ANALYSIS OF MANGROVE ECOSYSTEM FOR ECOFISHERYTOURISM IN SIDOARJO LUMPUR ISLAND - Yanelis Prasenja; Abimanyu Takdir Alamsyah; Dietriech G. Bengen (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Sidoarjo Lumpur Island is an artificial island created as a solution to the handling of sediment deposition in Porong River Estuary as a result of the mudflow which flowed into the sea via the Porong River. Lumpur Island is currently utilized as a habitat for mangrove ecosystem extension as well as a site for  aquaculture with wanamina system (silvofishery). Ecofisherytourism is a way to utilize mangrove ecosystem for ponds silvofishery based on educational and economic approach to achieve the welfare of society. In addition, ecofisherytourism has a direct  benefit of preserving nature and the environment. The research objective was to evaluate the condition of the mangrove ecosystem and analyze the physical condition of the Sidoarjo Lumpur Island as a reference in developing the island as ecofisherytourism region. The methods used were a combination of quantitative and qualitative methods. Data were collected through analysis of aerial photographs, field measurements, observation and documentation. Mangrove ecosystem conditions in Lumpur Island was classified as good  to be utilized as ecotourism and fisherytourism . The highest elevation of the island is the tidal zone where mangroves grow well.                                                                                          Keywords: ecofisherytourism, mangrove, silvofishery